When place and generation matter: Understanding resident satisfaction in rural tourism - Can Zhang; Massoomeh Hedayati Marzbali (PLoS ONE, 2026)
The revitalization of traditional villages through rural tourism has emerged as an important pathway for achieving sustainable regional development worldwide. Although the benefits of tourism are widely acknowledged, limited research has explored how residents’ expectations and place-based perceptions influence satisfaction across generations. This study integrates expectation confirmation theory and place attachment theory to explore the influence of expectations, place identity, place attachment, and perceived value on resident satisfaction. Data from 245 residents in three traditional villages in Yongzhou, China, are analyzed using structural equation modeling and multi-group analysis. Results reveal a negative association between expectations and satisfaction, while perceived value mediates the effects of place identity and place attachment. Generational differences further moderate several key relationships, with older residents showing higher satisfaction. These findings deepen our understanding of resident attitudes toward rural tourism and provide practical guidance for inclusive, community-centered strategies that promote sustainable rural development in line with the United Nations Sustainable Development Goals 8, 11, and 12.